Educational assessment in Portugal - Fernandes, D. (Assessment in Education: Principles, Policy and Practice, 2009)
After living under a strong dictatorship for almost 50 years, Portugal has been a politically free country since 1974. Today, Portugal enjoys a constitutional democracy and has been a member of the European Union (EU) since 1986. Portugal lies in the south‐west of the European continent, bordering Spain in the north and east and abutting the Atlantic Ocean in the south and west. Portugal’s total area, including the Atlantic archipelagos of Madeira and the Azores, consists of almost 92,391 square kilometres. According to Gabinete de Informação e Avaliação do Sistema Educativo (GIASE) [Cabinet for Information and Evaluation of the Education System], Portugal’s population in the year 2000 was 10,256,658, with about 40% of the population living in urban centres. The age structure shows that 16% of the population falls in the 0–14 age span, 14.3% in the 15–24 age span, 53.4% in the 25–64 age span and 16.3% are older than 65 (GIASE 2004).